From Clash to Dialogue of Civilizations Finding Common Ground Between Civilizations Islamic and the West - Karwadi; Aninditya Sri Nugraheni; Shindy Lestari (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2021)
Civilization built on the principle of religion is certainly returned to its basic character, then what happens is not a clash of civilizations, but instead is the process of filling each other, complementing and influencing each other. In this framework, what must be built is to open space for the creation of dialogue between civilizations in order to fight for the meeting point of Western civilization and Islam globally, which also paves the way for the realization of mutual tolerance. The method used library research, collection techniques in this study, first select documents or literature related to research studies, secondary sources of data in this study are books that support the purpose about discussion of the dialogue of civilizations looking for common ground between Islamic civilization and the underlying west of Samuel P. Huntington's thesis. Procedures and stages of research that will be carried out by researchers in general there are three stages, namely the stage of preparation, implementation, reporting. In conducting data analysis, the author will use descriptive analysis These findings can mean a discussion about: 1) sketches of Islam's relationship with the West, 2) Islam and the West: conflicts or interests?, 3) dialogue of Islamic and Western civilizations: could it be?, 4) implications for diverse tolerance in Indonesia. So that the dialogue of Islamic and Western civilizations will be more able to understand the existence of ritual differences and produce mutual understanding and interpretation of diversity in the contemporary world.